PENGEMBANGAN SISTEM INFORMASI PENGARSIPAN KINERJA DOSEN ABK PRIMANIYARTA DENGAN METODE SDLC - Setlight, Durand Fernandito Freddy; Supriyanto, Supriyanto; Canon, Lidya Juwita Pratiwi (Jurnal Teknik Informasi dan Komputer (Tekinkom), 2025)
The management and archiving of lecturer performance data are crucial for accountability, professional development, and meeting higher education accreditation standards. In many universities, like ABK Primaniyarta, the collection and archiving of performance evidence (e.g., teaching, research, and community service reports) are often done manually. One of the key needs for ABK Primaniyarta is an archiving information system or e-repository. Therefore, this research focuses on the design and development of a lecturer performance archiving system based on the Software Development Life Cycle (SDLC) using the Waterfall model, which includes requirements analysis, design, implementation, testing, and maintenance. In this application, document input will be performed by lecturers acting as administrators/users. The main objective of this application is to facilitate lecturers in submitting their performance data to each other and to ensure it can be properly archived. Data collection techniques involved interviews with lecturers and observations of the existing document reporting and archiving system at ABK Primaniyarta. The outcome of this research is an official web-based information system for archiving and reporting lecturer performance at ABK Primaniyarta, eliminating the need for Email & Google Drive.